Hand-eye coordination, movement reaction time and hand tactile sensitivity depending on the practiced sports discipline - Kaluga, E.; Straburzynska-Lupa, A.; Rostkowska, E. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Practicing competitive sports, particularly those disciplines in which the upper limbs are involved in the movement, develops physical fitness and its special feature, namely the hand-eye coordination. Some sport disciplines require manipulation of an object. Using a sport equipment every day, several times, during training and matches must affect the characteristics of the skin of the palmar side of the hand. It may be presumed to affect the tactile sensitivity of the skin. The aim of the study was to determine the relationship between hand-eye coordination and tactile sensitivity in basketball, volleyball, handball, football and combat sports players as compared to those who do not practice competitive sports. METHODS: Overall, 121 men were subject to tests. The tactile sensitivity threshold was determined at three points of the palmar side of the hand using The Touch-Test™ Sensory Evaluators esthesiometer. The second test involved hand-eye coordination of the upper limbs and it was carried out using cross-type machine. RESULTS: The greatest tactile sensitivity was shown in combat sports players. These players also demonstrated the shortest reaction time and the lowest number of errors in the motor coordination test. The correlation between tactile sensitivity and coordination was found to be the strongest in subjects not practicing sports. CONCLUSIONS: The most interesting finding is that in the group of athletes using hands (team sports games and combat sports) the correlation between movement coordination and tactile sensitivity is weaker.